Technical determinants of tackle and ruck performance in International rugby union - Hendricks, S.; van Niekerk, T.; Wade Sin, D.; Lambert, M.; den Hollander, S.; Brown, J.; Maree, W.; Treu, P.; Till, K.; Jones, B. (Journal of Sports Sciences, 2018)
The most frequently occurring contact events in rugby union are the tackle and ruck. The ability repeatedly to engage and win the tackle and ruck has been associated with team success. To win the tackle and ruck, players have to perform specific techniques. These techniques have not been studied at the highest level of rugby union. Therefore, the purpose of this study was to identify technical determinants of tackle and ruck performance at the highest level of rugby union. A total of 4479 tackle and 2914 ruck events were coded for the Six Nations and Championship competitions. Relative risk ratio (RR), the ratio of the probability of an outcome occurring when a characteristic was observed (versus the non-observed characteristic), was determined using multinomial logistic regression. Executing front-on tackles reduced the likelihood of offloads and tackle breaks in both competitions (Six Nations RR 3.0 Behind tackle, 95% confidence interval [95% CI]: 1.9-4.6, effect size [ES] = large, P < 0.001); Championship RR 2.9 Jersey tackle, 95% CI: 1.3-6.4, ES = moderate, P = 0.01). Fending during contact increased the chances of offloading and breaking the tackle in both competitions (Six Nations RR 4.5 Strong, 95% CI: 2.2-9.2, ES = large, P = P < 0.001; Championship RR 5.1 Moderate, 95% CI: 3.5-7.4, ES = large, P < 0.001). For the ruck, actively placing the ball increased the probability of maintaining possession (Six Nations RR 2.2, 95% CI: 1.1-4.3, ES = moderate, P = 0.03); Championship RR 4.0, 95% CI: 1.3-11.8, ES = large, P = 0.01). The techniques identified in this study should be incorporated and emphasised during training to prepare players for competition. Furthermore, these techniques need to be added to coaching manuals for the tackle and ruck.